Olive tree leaves - a source of valuable active compounds - Safarzadeh Markhali, Fereshteh (2020)
The agricultural and processing activities of olive crops generate a substantial amount of food by-products, particularly olive leaves, which are mostly underexploited, representing a significant threat to the environment. Olive leaves are endowed with endogenous bioactive compounds. Their beneficial/health-promoting potential, together with environmental protection and circular economy, merit their exploitation to recover and reuse natural components that are potentially safer alternatives to synthetic counterparts. These biomass residues have great potential for extended industrial applications in food/dietary systems but have had limited commercial uses so far. In this regard, many researchers have endeavoured to determine a green/sustainable means to replace the conventional/inefficient methods currently used. This is not an easy task as a sustainable bio-processing approach entails careful designing to maximise the liberation of compounds with minimum use of (i) processing time, (ii) toxic solvent (iii) fossil fuel energy, and (iv) overall cost. Thus, it is necessary to device viable strategies to (i) optimise the extraction of valuable biomolecules from olive leaves and enable their conversion into high added-value products, and (ii) minimise generation of agro-industrial waste streams. This review provides an insight to the principal bioactive components naturally present in olive leaves, and an overview of the existing/proposed methods associated with their analysis, extraction, applications, and stability.